The treatment of gastrointestinal fistalas with a somatostatin analogue SMS 201-995 - Kadir BAHAR; Süleyman BÜYÜKBERBER; M. Tuğrul SEZER; Şükrü DUMLU; Eyüp SELVİ; Ali ÖZDEN (Turkish Journal of Gastroenterology, 2020)
-